From a stone to rupture: calyceal rupture secondary to obstructive uropathy. Issue 6 (25th April 2018) - Kheiri, Babikir; Kazmi, Ismail; Madala, Seetharamprasad; Abu Sitta, Emad
Key Clinical Message: Renal collecting system rupture is a rare manifestation of obstructive uropathy. The majority of cases are attributed to ureteric calculi and extrinsic ureteric compression. The optimal diagnostic image is contrast‐enhanced CT scan with delayed phase protocol. Management is usually conservative and generally depends on the etiology, urinomas size, and the presence or absence of kidney failure or infections. Abstract : Renal collecting system rupture is a rare manifestation of obstructive uropathy. The majority of cases are attributed to ureteric calculi and extrinsic ureteric compression. The optimal diagnostic image is contrast‐enhanced CT scan with delayed phase protocol. Management is usually conservative and generally depends on the etiology, urinomas size, and the presence or absence of kidney failure or infections.